Termodinâmica de um conjunto de partículas em um bilhar bidimensional dependente do tempo: um gás bidimensional simplificado - Gália, Marcus Vinícius Camillo [UNESP] (2016)
This work was motivated by a one-dimensional model called as bouncer. The model consists of a particle moving under the action of a gravitational field and experiences collisions with a periodic moving platform. We describe shortly its dynamical properties and move forward to a two-dimensional billiard problem of the oval-like shape. The objective of this dissertation is to study some statistical and thermodynamical properties of an oval-like shaped billiard whose boundary moves in time. Upon collision with the boundary, the particle has a fractional lose of energy produced by inelastic collisions. We then obtain equations that describe the dynamics at both sort and large time. By the use of equipartition theorem, we make a connection of the dynamical results with the thermodynamics approach. In this dissertation we present an alternative way of making the connection with thermodynamics via the Fourier’s law for heat conduction.